Understanding Medication Adherence in Patients with Limited English Proficiency - Kahler, Luke; LeMaster, Joseph (Kansas Journal of Medicine, 2022)
Introduction. Approximately 41.6% of the US population who speak a language other than English (20% over all) and have limited English proficiency (LEP) status.1 Health outcomes for patients with LEP status or who are language discordant (speak a different language than their clinicians) have been studied in several settings, including the hospital and outpatient, with results widely demonstrating that these patients have worse outcomes when a professional interpreter is not used consistently. 2,3 The aim of this study was to investigate the impact of preferred language and language discordance on medication adherence. Methods. Data were collected via review of pharmacy-acquired medication profiles for three primary language cohorts: Nepali, Spanish, and English. Total Days of Adherence, Adherence Ratio, and Maximum Days Non-adherent were calculated and compared between language groups. We examined these statistics for regular and long-acting insulin, metformin and ACE inhibitors, testing for differences between language groups and those who experienced greater vs less than the median value for language concordant clinical encounters. Results. The most adherent group over all (highest adherence-ratio) were the Nepali-speaking, but the results showed high variability across outcomes and medications. Conclusions. After adjustment and stratification for greater vs lesser language concordant patient visit experience, we found that language-spoken plays an important role in the clinical encounter, and that LEP patients could have improved outcomes in their adherence to medications by having providers who speak their language or use an interpreter.